Shifting modes: Spectatorship, theatrical virtual reality and motion capture through the experience of Fatherland XR. Issue 1 (1st December 2019) - Smith, Matt
AbstractThis article discusses a project using Extended Reality (XR) within theatre and its effect on audiences who are part of the testing and development of a theatrical production. The article develops knowledge surrounding agency/embodiment and multimodal story telling utilizing virtual reality (VR) and motion capture technologies. There is also contained within the article a demonstration of how a university and a theatre company can collaborate using XR technologies. This collaboration is presented based on three interviews with key members of the team. At the time of writing the production is still undergoing final developments. The discussion places the practice within the field of immersive performance and new technologies. Many of the claims made are based on practice-based experiences and the messy data provided by test audiences who are asked to freely respond after the showings. The multiplicity of reactions to this performance artwork are discussed in relation to the emergent, accidental and playful results of multimodal practices often presenting themselves as a set of performative frames instead of a synergistic whole.